Turk Arch Pediatrics 2022
DOI: 10.5152/turkarchpediatr.2022.21368
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Face of Familial Mediterranean Fever

Abstract: Objective: Familial Mediterranean fever is a systemic inflammatory disease characterized by recurrent attacks in the form of fever and inflammation of serous membranes. We aimed to search for neurological signs and symptoms of children with familial Mediterranean fever. Materials and Methods: Medical records database from 2010 to 2020 was screened retrospectively. In total, 625 children with familial Mediterranean fever were included in the study. Neurological symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…However, the genetic aetiology of FMF is complex; it is not only caused by pathogenic variations, PPVs and VUSs, but also by the interaction with epigenetic factors and other genes [ 9 ]. Neurological symptoms defined in FMF are headache, myalgia, syncope, recurrent meningitis, vertigo, seizures, paraesthesia, demyelinating diseases, cerebrovascular diseases, posterior encephalopathy, prolongation of subclinical visual evoked potentials, pseudotumor cerebri and optic neuritis [ 5 ]. In a previous study reviewing risky genes for dystonia, the MEFV gene was not listed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the genetic aetiology of FMF is complex; it is not only caused by pathogenic variations, PPVs and VUSs, but also by the interaction with epigenetic factors and other genes [ 9 ]. Neurological symptoms defined in FMF are headache, myalgia, syncope, recurrent meningitis, vertigo, seizures, paraesthesia, demyelinating diseases, cerebrovascular diseases, posterior encephalopathy, prolongation of subclinical visual evoked potentials, pseudotumor cerebri and optic neuritis [ 5 ]. In a previous study reviewing risky genes for dystonia, the MEFV gene was not listed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic aetiology of FMF is complex, as epigenetic factors and interactions with other genes occur [ 4 ]. It was reported that neurological disorders are also detected as well as the symptoms of FMF in patients with MEFV variations, but dystonia is not among these symptoms [ 5 ]. In a large-scale review [ 6 ], genes with risk factors for dystonia were identified, but MEFV was not included in this list.…”
Section: Introductionmentioning
confidence: 99%